H.D.’s Palimpsest and a weaving practice: Weaving as method in literary studies - Infeld, Jordana (FormAkademisk, 2021)
The relationship between text and textile is ancient and multi-faceted. This paper aims to extend this relationship by placing a weaving practice in dialogue with H.D.’s novel Palimpsest. Weaving has a distinctive relationship with time, and therefore provides fertile ground for thinking through the way time is depicted in literary fiction. Time operates in weaving at various scales and rhythms, and Palimpsest furthers this understanding of time through its own rhythms and invocations of the image of the palimpsest. Drawing on my own weaving practice, my aim is to provide an account of how a craft practice might enable a particular method of reading texts that extends beyond traditional close reading methods.